ANALYSIS OF ENERGY CONCEPTS THROUGH PHET SIMULATION: A CASE STUDY ON SKATE PARK - Sudirman, Sudirman; Marwoto, Putut; Nugroho, Sunyoto Eko (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2024)
This study aims to analyze students' understanding of energy concepts through the PhET simulation in the case of the Skate Park. Energy concepts, including kinetic energy, potential energy, and mechanical energy, often present challenges in physics education, particularly in the context of visual and interactive comprehension. In this study, the PhET